CARACTERIZAÇÃO QUÍMICA DO SOLO EM UMA ÁREA DE RECUPERAÇÃO DE UM DEPÓSITO DE METALURGIA DE ZINCO - Oliveira Junior, Ailton Batista; Mendes, Erika Vanessa Cardoso; Figueiredo, Luiz Henrique Arimura; Fogaça, Cristiane Alves; Horn, Heinrich Adolf (Geochimica Brasiliensis, 2020)
Ore processing generates a large amount of sterile and waste from purification and concentration processes. This material, in contact with the environment, can cause major environmental impacts. CMM-Votorantim at Três Marias benefits silicate and sulphide Zn ores. The tailings from one stage of the process are deposited in an area called PH9 on the banks of the São Francisco River and subsequently removed and placed in a waterproofed settling basin. The area of the old deposit presented problems in the process of environmental recovery and, therefore, it became opportune to investigate chemically the level of contamination there. The area has 14.4 ha and is located in the municipality of Três Marias / MG with a slope towards the bed of the São Francisco River. The soil samples were collected in two cross profiles, one North - South and the other East - West, totaling 29 georeferenced points with a distance of 20 m. A soil sample was collected at each point. After preparation at the Soil Laboratory of Unimontes, Campus Janaúba - MG, the samples were analyzed in the ICP OES laboratory of the NGqA of the CPMTC of UFMG - Campus Belo Horizonte. Total and available concentrations of calcium, magnesium, aluminum, iron, manganese, copper, zinc and organic matter, together with pH were determined. For the graphical representation, we opted for a grouping the results in pH ranges versus concentrations. The results show that the area has magnesium contamination, thus causing severe structural degradation of the soil. The concentrations of the other elements in the PH9 area are within the limits allowed for land use in agricultural activity, but approaching the upper limit allowed.